2021
DOI: 10.1101/2021.01.27.428396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved spatio-temporal measurements of visually-evoked fields using optically-pumped magnetometers

Abstract: Recent developments in performance and practicality of optically pumped magnetometers have enabled new capabilities in non-invasive brain function mapping through magnetoencephalography (MEG). In particular the lack of need of cryogenic operating conditions allows for more flexible placement of the sensor heads closer to the brain surface, leading to improved spatial measurement resolution and increased source localisation capabilities. Through recordings of visually evoked brain fields (VEF) we demonstrate th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Magnetoencephalography: MEG is a nerve imaging technology that can measure the magnetic field near the head. [13,46,47] Recent studies have shown that MEG can be used to evaluate neurological diseases such as Alzheimer's disease, [48] Parkin-son´s disease, [49] and autism spectrum dysfunction. [50] Despite their considerable potential, existing MEGs also exhibit significant limitations.…”
Section: Output-type Bcismentioning
confidence: 99%
See 3 more Smart Citations
“…Magnetoencephalography: MEG is a nerve imaging technology that can measure the magnetic field near the head. [13,46,47] Recent studies have shown that MEG can be used to evaluate neurological diseases such as Alzheimer's disease, [48] Parkin-son´s disease, [49] and autism spectrum dysfunction. [50] Despite their considerable potential, existing MEGs also exhibit significant limitations.…”
Section: Output-type Bcismentioning
confidence: 99%
“…Besides, the use of MEG is confined to magnetically shielded rooms (MSR), [13] because it needs MSR to suppress the magnetic noise from the environment, and this noise is typically many orders of magnitude higher than the neural magnetic field (fT to pT range). [51] State-of-the-art MEG systems employ around 300 SQUID, and the sensors are fixed around a patient's head. [52] In MEG, new sensors such as OPMs and high-T(c) SQUID have made it possible to sense the magnetic field on the scalp within millimeters from the scalp surface, as contrast to typical liquid-heliumcooled SQUID sensors that detect the field around ∼2 cm outside the scalp.…”
Section: Output-type Bcismentioning
confidence: 99%
See 2 more Smart Citations
“…SQUIDs require cryogenic cooling which increases costs, limits the device portability, and increases the separation between the device and object of interest. OPMs offer reduced separation distances over SQUIDs, which is of particular interest for magnetoencephalography (MEG) [4][5][6][7], where OPM-MEG is able to offer an improved spatial [8,9], and spatio-temporal [10] resolution. These advantages can be similarly applied to the diagnostic measurement of batteries through non-invasive current mapping [11,12], and for fundamental physics research [13,14].…”
Section: Introductionmentioning
confidence: 99%